The Effect of Peer Observation on Consumption Choices: Experimental Evidence - Antonia Grohmann; Sahra Sakha (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper investigates the impact of peer observation on consumption decisions of rural households in Thailand using a lab-in-the-field experiment. We find that observing groups show lower within group standard deviation. Thus, we provide evidence for conformity. Further, we find that individual's consumption choice is influenced by the group choice controlling for large number of individual, household, and village characteristics. Concerning the mechanisms, we observe that unfamiliarity of the consumption good is counteracted by peer effects. We further show that the consumption choice is influenced by how many people made the same decision previously, but not by who made that decision.
Keywords: D12; C21; C92; 330; Consumption; Peer Effects; Conformity